STUDI KANDUNGAN BEBERAPA ZAT GIZI DAN SIFAT ORGANOLEPTIK BISKUIT BERBASIS TEPUNG KOMPOSIT PUTAK DAN KACANG KOMAK - Boeky, Daniela L. A.; Aspatria, Utma; Markus, JER (Pergizi Pangan DPD NTT, 2011)
The research was knowing nutrient content and organoleptic characteristic of biscuit based on composite fluor of putak and Dolichos bean (Lablab purpureus). Completely Randomized Design of 6 treatments and 2 replications was applied. The treatments used were (A) 100% putak, (B) 70% putak + 30% dolichos bean, (C) 60% putak + 40% dolichos bean, (D) 50% putak + 50% dolichos bean, (E) 40% putak + 60% dolichos bean, and (F) 30% putak + 70% dolichos bean. Variable measured were energy, carbohydrate, protein, fats, moisture and ash contents and organoleptic characteristic were odor, colour, taste and texture. Data obtained were analyzed using ANOVA and Least Significant Difference (BNT) 5%. The result show that the treatments were significantly (P<0,05) effected on the energy, carbohydrate, protein, moisture and ash contents but not significantly (P>0,05) on the fats contents. The organoleptic test showed that treatment (D) 50% putak + 50% dolichos bean was the best treatment. In conclusion, added Dolichos bean flour on the putak increasing the biscuit energy, carbohydrate, protein, moisture and ash contents significantly (P<0,05) but not increasing and not significantly (P>0,05) the fats contents.